Uma arquitetura com suporte a módulos dinâmicos para WebLab no domínio de redes de computadores - Souza, Daniel Vieira de (2011)
This work presents an architecture that supports dynamic modules for Remote Access laboratories (WebLab) in the domain of computer networks. The architecture follows the paradigm of Service Oriented Architecture (SOA). The experiments are available as modules, following the OSGi specification (Open Services Gateway Initiative). The services of each module of the experiment are automatically published asWeb services, following the REST (Representational State Transfer) principles. Functional requirements for general-purpose WebLabs, as well for the domain of computer networks, are covered in this proposal in order to allow the creation of more robust WebLab that meets the demand of use on the part of students and educational institutions, and in a scalable manner. Through the creation of a new experiment, which made use of the reference implementation of the proposed architecture, it was allowed to demonstrate the facility in designing andmaking available the experiments in the form of modules, besides contributing to the WebLab with one more experiment that allows setting up VLANs (Virtual Local Area Network).